Literature review on the effect of restrictiveness of trade in services on economic growth - Othman, Zalila; Mohd Mohaideen, Zalina; Ahmad Samidi, Munzarina (Universitas Islam Riau Indonesia, 2010)
Economic growth is one of the most important objectives of macroeconomic policies of every country in the world. Various factors such as investment in physical capital, investment in human capital, and prudent fiscal and monetary policies, contribute to economic growth. Trade policy is another important factor determining economic growth. Trade openness may influence growth via access to new technologies from abroad. However, external trades have usually been subjected to various tariffs and non-tariffs barriers, erected for various reasons. The quantification of barriers to services trade is one of the most pressing issues in services trade since barriers to trade in services are mostly nontariffs in nature. Researchers have come up with various indices to measure restrictiveness in services trade. The indices can subsequently be included in a growth regression to show its significance in influencing economic growth rates. This paper will demonstrate that empirically, studies have mostly provide evidence that an outer-oriented or more open economies experienced higher growth rates compared to inward-oriented economies (see Barro, 1991; Dollar, 1992; Edwards, 1992, 1993, 1998; Frankel and Romer, 1999; Sachs and Warner, 1995; among others).